2012
DOI: 10.1177/0192512112462971
|View full text |Cite
|
Sign up to set email alerts
|

The duration and durability of cabinet ministers

Abstract: This article surveys the growing research programme on the duration of cabinet ministers. It examines some of the conceptual and methodological issues confronting research, including the nature and measurement of durability, ministerial terms and techniques. It considers some of the theories and hypotheses that have been generated by researchers. Using evidence from studies from around the world, it argues that institutional factors, including regime type, constitutional and parliamentary rules, and party syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 32 publications
3
46
0
5
Order By: Relevance
“…A number of studies have found that ministers with parliamentary experience are less prone to dismissal than their colleagues (Bäck et al ; Fischer & Kaiser ; Bucur ). Fischer et al (, 209) argue that this is a consequence of ministers having worked their way through the party and proven themselves worthy before entering office. Parliamentary experience is – because of violations to the proportional hazard assumption – coded as a dichotomous variable, scoring 1 for ministers with more than 30 days of parliamentary experience and 0 for ministers with less time in parliament than this.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found that ministers with parliamentary experience are less prone to dismissal than their colleagues (Bäck et al ; Fischer & Kaiser ; Bucur ). Fischer et al (, 209) argue that this is a consequence of ministers having worked their way through the party and proven themselves worthy before entering office. Parliamentary experience is – because of violations to the proportional hazard assumption – coded as a dichotomous variable, scoring 1 for ministers with more than 30 days of parliamentary experience and 0 for ministers with less time in parliament than this.…”
Section: Methodsmentioning
confidence: 99%
“…In line with the parliamentary experience variable, I also control for youth party experience among former MPs. If Fischer et al's (, 209) explanation holds, this variable should have an even bigger effect than parliamentary experience on ministerial durability because these are the hard‐core party members that have worked their way through the youth organization, claimed parliamentary seats and finally been rewarded with cabinet portfolios. The youth party variable is a combination of the two youth experience variables used by Eilertsen (): if the minister has experienced either local or central/national youth party organization he or she is given the score of one; they are given a score of zero for no youth party experience.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Fischer, Dowding, and Dumont (2012) speculate that female ministers have higher career durations than their male counterparts because they need to be especially talented in order to reach these top posts. As female party leaders are among a small subset of politicians who have excelled despite these challenges, those who perform well in the face of this adversity may actually, on average, outlast men.…”
Section: Hypothesizing About Performance and Women's Tenure As Leadersmentioning
confidence: 99%
“…As female party leaders are among a small subset of politicians who have excelled despite these challenges, those who perform well in the face of this adversity may actually, on average, outlast men. Indeed, Fischer, Dowding, and Dumont (2012) speculate that female ministers have higher career durations than their male counterparts because they need to be especially talented in order to reach these top posts. This suggests:…”
Section: Hypothesizing About Performance and Women's Tenure As Leadersmentioning
confidence: 99%
“…The overall assumption is that, all else equal, different individuals occupying similar political offices will select (and deselect) individuals with similar professional profiles, irrespective of their own personal preferences. A common measurement of experience and performance in office is individual tenure (e.g., Berlinski et al, 2012;Fischer et al, 2012;Bright et al, 2015).…”
Section: Agency and Political Careers: Actor-oriented Approachesmentioning
confidence: 99%